Targeting the polyene chain represents an adjuvant strategy for optimizing polyene antifungals - Yishan Zhang; Xiaocong Liu; Luobei Weng; Shuixiu Li; Peiran Chen; Gehua Zhang; Jianqi Wang; Dongmei Zhang; Chuanyan Tang; Yunfeng Hu; Wencai Ye; Hong Zhang (Proceedings of the National Academy of Sciences, 2026)
Polyene antifungals (PAs) have long constituted an irreplaceable lifesaving treatment for lethal fungal infections. However, PAs induce significant dose-dependent nephrotoxicity, primarily because of their binding to cholesterol in the renal cell membrane, which is structurally similar to their fungicidal target ergosterol in the fungal membrane. Efforts to optimize PAs have focused mainly on their mycosamine group and polyol chain, while the potential of the polyene chain remains underexplored. Here, we report that the polyene chain can function as a molecular switch, enabling hydrophobic coupling with structurally compatible adjuvants repurposed from clinically approved drugs. This hydrophobic coupling triggers conformational rearrangements of PAs, which are characterized by a reorientation of the mycosamine group, and increases the rigidity and length of the polyene chain, which can asymmetrically modulate the binding of PAs to membrane cholesterol and ergosterol, thereby attenuating nephrotoxicity and increasing effectiveness. Among them, vitamin D 3 demonstrated immediate clinical value, characterized by its broad safety profile and substantial dual adjuvant activities in multiple animal models and retrospective clinical data. Thus, exploiting the polyene chain as a molecular switch, modulated via specific polyene chain–coupled adjuvants, is a strategy to concurrently attenuate nephrotoxicity and potentiate the effectiveness of PAs.